Undergraduate students’ mathematical reasoning in numeracy-based tasks: A Rasch model approach - Dewi Hamidah; Jerhi Wahyu Fernanda; Zun Azizul Hakim; Galuh Nuril Lathifah (Jurnal Elemen, 2026)
Mathematical reasoning is essential in higher education because it enables students to formulate conjecture, generalize patterns, and justify. This study examined undergraduate students’ mathematical reasoning, operationalized through conjecturing, generalizing, and justifying, in two numeracy tasks. A purposive sample of 185 mathematics education students from the first, third and fifth semesters at a State University in Kediri, Indonesia, participated in the study. Responses were scored using an analytic rubric and analyzed with the Rasch model to estimate item difficulty and person ability, evaluate item fit and reliability, and examine Differential Item Functioning (DIF) across gender, Grade Point Average (GPA), and semester level. The results indicated that conjecturing and justifying were the most challenging aspects for students, while evidence of generalizing was relatively limited. Rasch analysis verified the instrument’s validity and reliability, with all items satisfying fit requirements, while DIF analysis indicated no significant demographic bias. However, observed patterns suggested that female students tended to be more systematic and accurate, male students were generally more flexible but less consistent, and students with higher GPAs displayed stronger logical reasoning. These findings highlight the importance of instructional strategies that intentionally foster mathematical reasoning and suggest future research involving multiple institutions and longitudinal designs.